2017
DOI: 10.2196/mental.8139
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Family Life Information Through Video Calls and Other Information and Communication Technologies and the Association With Family Well-Being: Population-Based Survey

Abstract: BackgroundThe use of information and communication technologies (ICTs) for information sharing among family members is increasing dramatically. However, little is known about the associated factors and the influence on family well-being.ObjectiveThe authors investigated the pattern and social determinants of family life information sharing with family and the associations of different methods of sharing with perceived family health, happiness, and harmony (3Hs) in Hong Kong, where mobile phone ownership and In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 45 publications
8
32
1
1
Order By: Relevance
“…Yang, Neustaedter, & Schiphorst, 2017, May;Sirin, & Deniz, 2016;Eğeci, & GençÜz, 2006). Kesejahteraan dan keharmonisan rumah tangga dapat terjalin dan tercipta dengan adanya komunikasi interpersonal yang baik dari masing-masing anggota keluarga itu sendiri, terutama komunikasi yang terjalin antara suami dan istri Sincihu, Maramis, & Rezki, 2018;Shen, Wang, Chu, Wan, Viswanath, Chan, & Lam, 2017 Berkomunikasi artinya menyampaikan pesan kepada orang lain. Pesan komunikasi dapat mempunyai banyak bentuk, baik dalam bentuk verbal/lisan dan tulisan serta dalam bentuk komunikasi secara nonverbal/tanpa kata (DeVito, 2011).…”
Section: Resultsunclassified
“…Yang, Neustaedter, & Schiphorst, 2017, May;Sirin, & Deniz, 2016;Eğeci, & GençÜz, 2006). Kesejahteraan dan keharmonisan rumah tangga dapat terjalin dan tercipta dengan adanya komunikasi interpersonal yang baik dari masing-masing anggota keluarga itu sendiri, terutama komunikasi yang terjalin antara suami dan istri Sincihu, Maramis, & Rezki, 2018;Shen, Wang, Chu, Wan, Viswanath, Chan, & Lam, 2017 Berkomunikasi artinya menyampaikan pesan kepada orang lain. Pesan komunikasi dapat mempunyai banyak bentuk, baik dalam bentuk verbal/lisan dan tulisan serta dalam bentuk komunikasi secara nonverbal/tanpa kata (DeVito, 2011).…”
Section: Resultsunclassified
“…Making phone calls and using other means of communication, including social media, is a much cheaper way to get in touch with families at home. Previous studies reported that the use of smartphones as a family life communication tool was associated with family wellbeinghealth, happiness, and harmony (Guo et al, 2019;Shen et al, 2017). Furthermore, maintaining family functions and effectively coping with family problems may support the survival of nurse migrants in other counties.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents with higher SES status may use eDevice more because of longer work-related use. In our previous study, respondents with higher SES status used eDevice more frequently for health and family information seeking and sharing [ 24 ], and communicated with family members more via phone calls, instant messaging (IM), and video calls [ 9 , 10 ]. Higher SES status respondents had higher access to eDevice, which may also lead to greater use [ 24 ].…”
Section: Discussionmentioning
confidence: 99%